DETERMINATION OF VELOCITY AND DIRECTION OF GROUND WATER BY RADIOACTIVE TRACERS - CHANDRA, UMESH; AOKI, PEDRO EITI; E SILVA, JOÃO AUGUSTO RAMOS; CASTAGNET, ANTÔNIO G. (Águas Subterrâneas, 1980)
RESUMO NÃO DISPONIVEL